2011
DOI: 10.1128/jcm.00138-11
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Xpert MTB/RIF and Genotype MTBDR plus for Patient Selection for a Tuberculosis Clinical Trial

Abstract: Participation criteria for clinical trials in pulmonary tuberculosis commonly include confirmation of sputum positive for mycobacteria and an indication of drug susceptibility before treatment is initiated. We investigated the suitability of two novel sputum-based nucleic acid amplification methods for patient selection in a recent early bactericidal activity study. Spontaneously expectorated sputum samples of 140 consecutive pulmonary tuberculosis patients were examined with direct fluorescence microscopy, Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…There is a large number of studies evaluating Xpert on pulmonary specimens [5,6,[17][18][19][20][21][22][23]; the sensitivity varies from 95% to 100% in smear-positive sputa, and from 47% to 77% in smear-negative ones. Our data score high within these ranges, despite the well-known lower yield of extrapulmonary samples in term of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large number of studies evaluating Xpert on pulmonary specimens [5,6,[17][18][19][20][21][22][23]; the sensitivity varies from 95% to 100% in smear-positive sputa, and from 47% to 77% in smear-negative ones. Our data score high within these ranges, despite the well-known lower yield of extrapulmonary samples in term of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the performance of the Xpert assay in comparison with those of other molecular assays for either respiratory or nonrespiratory specimens (4)(5)(6)(10)(11)(12). In those studies, the Xpert assay showed performance comparable with that of other molecular assays for respiratory specimens with sensitivities reported between 79 and 93%, while those of other assays ranged from 76 to 96.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have described the analytic and clinical performance of Xpert MTB/RIF (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Several small studies have compared quantitative Xpert MTB/RIF results with more conventional measures of bacterial load, such as direct or concentrated sputum smears, counts of cfu on solid agar growth media, or measures of time-to-detection (TTD) in liquid culture (11,13,14,16). However, these studies have been performed at single sites with limited numbers of samples, which has precluded detailed and generalizable analyses.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%